قراءة نقدية لقانون مناهضة العنف الأسري لإقليم كوردستان - العراق المرقم 8 لسنة 2011 - عزيز, سردار علي (Journal of Legal and Political Studies, 2013)
To issue an integral legislation certain bases have to be taken in consideration, including the principle of the balance of interests . And also includes creating the conditions for issuing legislation intended to do the preparatory work that makes the new legislation acceptable to the members of society . As well as texts explicitly and precisely which requires that the legislature issued his/her provisions or laws clearly, precisely and detailed . And determine the penalty of each criminal behavior separately based on its risk. It is noticeable that the legislature when legislate the law of Against Domestic Violence in Kurdistan Regional N.8 2011, bucked the majority of the bases mentioned, where this legislation bucked the principle of legality of offenses and penalties, in the article (II / I) of this law . The legislator in this law deals with domestic violence crimes as serious and one which is no difference between them.
Keywords: principle of the balance of interests; Criminal behavior; Legislation; Penalties